Phosphorus sulfonate compound modified perovskite thin film and photovoltaic cell
Patent Information
- Application Number
- CN202311283684.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-10-07
- Publication Date
- 2026-10-30
- Estimated Expiration
- 2043-10-07
AI Technical Summary
[0004]有鉴于此,本申请提供了一种磷磺酸盐类化合物改性钙钛矿薄膜和光伏电池,用于解决现有技术中钙钛矿薄膜在高温和高湿环境下稳定性不好的技术问题
[0022]需要说明的是,本申请提供的光伏电池为钙钛矿光伏电池,结构为现有常规结构,由于吸光层包括上述磷磺酸盐类化合物改性钙钛矿薄膜,磷磺酸盐类化合物改性钙钛矿薄膜中磷酸盐保护层富集在钙钛矿晶粒晶界处,从而使得光伏电池的吸光层在高温和高湿环境下稳定,不容易分解,从而使得基于该种磷磺酸盐类化合物改性钙钛矿薄膜的光伏电池光电转化效率高,能够作为商业化光伏电池应用。
Smart Images

Figure CN117202684B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of photovoltaic cell material technology, and particularly relates to a perovskite thin film modified with a phosphate sulfonate compound and a photovoltaic cell. Background Technology
[0002] The increasingly serious depletion of fossil fuels has spurred the development of renewable energy. Among renewable energy sources such as wind, solar, and hydropower, solar energy has attracted much attention due to its huge reserves and ease of use. Using solar cell devices to generate electricity has become a way to alleviate the shortage of fossil fuels. Currently, commercial solar cell devices are mainly silicon-based. However, due to factors such as complex manufacturing processes and high costs, the further development of silicon-based solar cell devices faces great obstacles. This has driven the development of thin-film solar cells, which are easier to manufacture and have lower costs, such as perovskite solar cells and copper indium selenide thin-film solar cells.
[0003] Perovskite thin film-based solar cells have the potential for commercial application due to their high photoelectric conversion efficiency and ease of fabrication. However, perovskite thin films have poor stability and are difficult to maintain their original structure under high temperature or high humidity conditions. The films are prone to decomposition, which leads to a decrease in the photoelectric conversion efficiency of the solar cells. Summary of the Invention
[0004] In view of this, this application provides a perovskite thin film and a photovoltaic cell modified with phosphosulfonate compounds to solve the technical problem of poor stability of perovskite thin films under high temperature and high humidity environments in the prior art.
[0005] The first aspect of this application provides a method for preparing perovskite thin films modified with phosphonate sulfonate compounds, the method comprising the following steps:
[0006] Step S1: Dissolve lead halide, formamidinium halide and phosphonate compounds in an organic solvent to obtain a phosphonate-modified perovskite precursor solution.
[0007] Step S2: Spin-coating the perovskite precursor solution modified with phosphonate compounds to prepare a wet film of perovskite precursor modified with phosphonate compounds.
[0008] Step S3: Anneal the phosphate sulfonate modified perovskite precursor wet film at 50-70°C for 1-5 minutes to obtain a one-step annealed phosphate sulfonate modified perovskite precursor wet film.
[0009] Step S4: Anneal the wet film of the perovskite precursor modified by the phosphate sulfonate compound obtained in one step at 110-125°C for 10-40 minutes to obtain the perovskite precursor film modified by the phosphate sulfonate compound.
[0010] Preferably, step S3 specifically includes: annealing the phosphonate-modified perovskite precursor wet film at 65°C for 1 minute to obtain a one-step annealed phosphonate-modified perovskite precursor wet film.
[0011] Step S4 specifically includes: annealing the phosphate sulfonate-modified perovskite precursor wet film at 120°C for 30 minutes to obtain a phosphate sulfonate-modified mixed perovskite precursor film.
[0012] Preferably, the phosphonate compound is selected from sulfonic acid Cy3 triphosphate and / or N-butylsulfonic acid pyridine dihydrogen phosphate.
[0013] Preferably, in step S1, the lead halide is selected from any one or at least two of lead chloride, lead iodide, and lead bromide;
[0014] The formamidine halide is selected from any one or at least two of formamidine chloride, formamidine bromide, or formamidine iodide;
[0015] Preferably, in step S1, the perovskite precursor solution modified with phosphosulfonate compounds includes 659.2 parts by mass of lead iodide, 245.9 parts by mass of formamidinium iodide, and 0.43 parts by mass of N-butylsulfonic acid pyridine dihydrogen phosphate.
[0016] Preferably, in step S2, the spin coating of the perovskite precursor solution modified with phosphonate compounds specifically includes: adding the perovskite precursor solution modified with phosphonate compounds and the antisolvent to the substrate, and then spin coating using a spin coater.
[0017] Preferably, in step S1, the organic solvent is selected from any one or at least two of N,N-dimethylformamide, dimethyl sulfoxide, and isopropanol;
[0018] In step S2, the antisolvent includes any one or at least two of chlorobenzene, anisole, ethyl acetate, and diethyl ether.
[0019] The second aspect of this application provides a perovskite thin film modified with a phosphonate sulfonate compound, which is prepared by the above-described preparation method.
[0020] A third aspect of this application provides a photovoltaic cell, comprising a conductive glass substrate, an electron transport layer, a perovskite absorber layer, a hole transport layer, and a metal top electrode stacked sequentially.
[0021] The perovskite absorber layer comprises the above-mentioned perovskite film modified with phosphosulfonate compounds.
[0022] It should be noted that the photovoltaic cell provided in this application is a perovskite photovoltaic cell with a conventional structure. Since the light-absorbing layer includes the aforementioned perovskite film modified with phosphate sulfonate compounds, the phosphate protective layer in the perovskite film is enriched at the grain boundaries of the perovskite grains. This makes the light-absorbing layer of the photovoltaic cell stable under high temperature and high humidity conditions and not easily decomposed. As a result, the photovoltaic cell based on this perovskite film modified with phosphate sulfonate compounds has high photoelectric conversion efficiency and can be used as a commercial photovoltaic cell.
[0023] In summary, this application provides a perovskite thin film and photovoltaic cell modified with phosphonate compounds. The phosphonate compounds contain hydrogen phosphate (dihydrogen phosphate) and sulfonic acid groups, which react with the perovskite components to form a hydrophobic phosphate complex protective layer through in-situ surface reconstruction. During crystallization and growth, a stepwise crystallization annealing process is used to control the precipitation location of this hydrophobic phosphate complex, resulting in a tightly packed grain boundary filling effect. This allows the generated phosphate complex protective layer to be regularly filled at the grain boundaries of the perovskite grains. The phosphate protective layer is enriched at the grain boundaries of the perovskite grains, while some of the protective layer also precipitates on the surface. This method achieves full passivation and protection of grain boundaries, greatly improving the temperature and humidity stability of perovskite films. Experiments show that the perovskite film modified with phosphonate compounds provided in this application can basically maintain its original structure after being heated at 85°C for 1600 hours or stored in an atmospheric environment with 40%-50% humidity for 4000 hours. The absorption of ultraviolet-visible light still maintains 83.9% of the initial absorption. This indicates that the perovskite film modified with phosphonate compounds provided in this application has good stability and can maintain its original structure under high temperature or high humidity environments, thereby solving the technical problem of poor stability of perovskite films under high temperature and high humidity environments in the prior art. Attached Figure Description
[0024] To more clearly illustrate the technical solutions in the specific embodiments of this application or the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of this application. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.
[0025] Figure 1 This is a schematic diagram of the preparation method of the perovskite thin film modified by phosphosulfonate compounds provided in Example 1 of this application;
[0026] Figure 2 X-ray diffraction pattern of the perovskite thin film modified with phosphosulfonate compounds provided in Example 1 of this application;
[0027] Figure 3Atomic force microscopy images of the perovskite thin films provided in Examples 1-3 of this application;
[0028] Figure 4 The phase diagrams are those of the perovskite thin films provided in Examples 1-3 of this application;
[0029] Figure 5 These are energy dispersive spectroscopy (EDS) line scans of the perovskite thin films provided in Examples 1-3 of this application;
[0030] Figure 6 Field emission scanning electron microscope (FESEM) images of the perovskite thin films provided in Examples 1-3 of this application;
[0031] Figure 7 X-ray diffraction patterns of the perovskite thin films provided in Examples 1-3 of this application after being heated at 85°C for 1600 hours;
[0032] Figure 8 The ultraviolet-visible absorption spectra of the perovskite thin films provided in Examples 1-3 of this application after being stored in an atmospheric environment with 40% humidity for 4000 hours;
[0033] Figure 9 Figures show the results of photoelectric efficiency and external quantum efficiency tests of perovskite solar cells assembled based on the perovskite thin films provided in Examples 1-3.
[0034] Figure 9 In the diagram, a is the photoelectric efficiency test graph of the perovskite solar cell provided in Examples 1-3 of this application, b is the external quantum efficiency test graph of the perovskite solar cell provided in Examples 1-3 of this application, and c is the photoelectric efficiency test efficiency and external quantum efficiency test data of the perovskite solar cell provided in Examples 1-3 of this application. Detailed Implementation
[0035] This application provides a perovskite thin film and a photovoltaic cell modified with phosphonate compounds to solve the technical problem of poor stability of perovskite thin films under high temperature and high humidity environments in the prior art.
[0036] The technical solutions of this application will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. Based on the embodiments of this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.
[0037] In this embodiment, the abbreviation is as follows:
[0038] BMDP-TSA: Phosphate sulfonate compound modification + synergistic two-step annealing process for perovskite thin films provided in the examples;
[0039] BMDP: Perovskite films modified with phosphonate compounds by a one-step annealing process using N-butylsulfonate pyridine phosphate dihydrogen phosphate as provided in the examples;
[0040] Control: The perovskite thin film provided in the examples is based on a conventional one-step annealing process.
[0041] Example 1
[0042] Given the poor stability of perovskite films in the prior art, their inability to maintain their original structure under high temperature or high humidity conditions, and the tendency for the films to decompose easily, Example 1 of this application provides a method for preparing perovskite films modified with phosphonate compounds. This method modifies the perovskite film to improve its stability. The method includes the steps of preparing a perovskite precursor solution modified with phosphonate compounds, preparing a wet film of the perovskite precursor modified with phosphonate compounds, and a two-step annealing process to prepare the perovskite film modified with phosphonate compounds.
[0043] The step of preparing the phosphorus sulfonate modified perovskite precursor solution includes: dissolving 659.2 parts by mass of lead iodide, 245.9 parts by mass of formamidinium iodide, and 0.43 parts by mass of N-butylsulfonic acid pyridine dihydrogen phosphate in 1 mL of a mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide, wherein the volume ratio of the solvent is N,N-dimethylformamide:dimethyl sulfoxide = 4:1, and stirring magnetically until completely dissolved to obtain the phosphorus sulfonate modified perovskite precursor solution;
[0044] The steps for preparing a wet film of perovskite precursor modified by phosphonate compounds include: using a pipette, measuring 50 μL of the perovskite precursor solution modified by phosphonate compounds, then dropping it onto the substrate to cover the substrate, and then spin-coating it using a spin coater while adding 120 μL of the anti-solvent chlorobenzene during the process to obtain a wet film of perovskite precursor modified by phosphonate compounds.
[0045] The two-step annealing process for preparing perovskite films modified with phosphonate compounds includes: placing a wet film of perovskite precursor modified with phosphonate compounds on a hot plate at 65°C for annealing for 1 minute, then transferring it to a hot plate at 120°C for annealing for another 30 minutes, and naturally cooling to obtain the perovskite film modified with phosphonate compounds. The perovskite film modified with phosphonate compounds treated by the two-step annealing process is designated as sample BMDP-TSA group.
[0046] Example 2
[0047] Example 2 of this application provides a method for preparing a perovskite thin film modified by phosphonate compounds. As a comparative example, the preparation method differs from that in Example 1 in that the step of annealing to prepare the perovskite thin film modified by phosphonate compounds is a one-step annealing, which is performed directly on a hot plate at 120°C for 30 minutes. The resulting perovskite thin film modified by phosphonate compounds is denoted as sample BMDP group.
[0048] Example 3
[0049] Example 3 of this application provides a method for preparing a perovskite thin film. As a comparative example, the preparation method differs from that of Example 1 in that it does not include the steps of adding N-butylsulfonic acid pyridine phosphate dihydrogen salt to prepare a perovskite precursor solution modified by phosphonate compounds and two-step annealing. That is, the preparation method is to dissolve lead iodide and formamidinium iodide in a mixed organic solvent of N,N-dimethylformamide and dimethyl sulfoxide to prepare a perovskite precursor solution modified by phosphonate compounds. Then, the perovskite precursor solution modified by phosphonate compounds is prepared into a wet film and annealed on a hot plate at 120°C for 30 minutes. The resulting perovskite thin film is designated as the Control group.
[0050] Experimental Example 1
[0051] Experimental Example 1 of this application performs performance tests on the perovskite thin films described in Examples 1-3. The performance tests include X-ray diffraction analysis, field emission scanning electron microscopy analysis, atomic force microscopy analysis, phase diagram analysis, energy dispersive spectroscopy line scan analysis, high temperature stability test, high humidity stability test, photoelectric efficiency test, and external quantum efficiency test.
[0052] Among them, X-ray diffraction analysis, such as Figure 2 As shown, Figure 2 The results show that during the preparation of perovskite films modified with phosphonate compounds, the addition of N-butylsulfonate pyridine phosphate dihydrogen salt as a modifying additive, combined with a two-stage annealing process, significantly improved the intensity of the 14.1° (100) main peak of the resulting perovskite film modified with phosphonate compounds (PSK-BMDP). This demonstrates that the crystal quality of the perovskite film modified with phosphonate compounds (sample BMDP-TSA group) provided in Example 1 has been improved, which is beneficial to improving the stability of the perovskite film.
[0053] Field emission scanning electron microscopy analysis, such as Figure 3 As shown, Figure 3The results show that, compared with the BMDP group perovskite film provided in Example 2 and the Control group perovskite film provided in Example 3, the BMDP-TSA group of phosphate sulfonate modified perovskite films provided in Example 1, due to the addition of the crystallization / passivation regulator N-butylsulfonate pyridine phosphate dihydrogen salt and the synergistic distribution annealing process, resulted in a significant increase in product grain size and a reduction in grain boundaries in the film, further demonstrating that its crystallinity was improved. At the same time, it can be clearly observed that a granular phosphate protective layer appeared on the perovskite surface after the addition of N-butylsulfonate pyridine phosphate dihydrogen salt, and this protective layer was concentrated at the perovskite grain boundaries after the stepwise crystallization annealing process.
[0054] Atomic force microscopy, phase diagram analysis, and energy dispersive spectroscopy (EDS) line scan analysis also showed similar analytical results, such as... Figure 4-6 As shown, Figure 4 Atomic force microscopy analysis showed that the perovskite film modified with phosphonate compounds had a smoother surface morphology, and obvious fillers were found at the grain boundaries of the perovskite. Further phase diagram analysis of the phosphonate-modified perovskite film... Figure 5 The phase diagram analysis shown reveals that the phase composition of the filler at the grain boundaries is different from that of the surrounding grains; energy dispersive spectroscopy (EDS) analysis shows... Figure 6 As shown, Figure 6 The results show that the phosphorus (P) signal is enhanced and the lead (Pb) signal is weakened at the grain boundaries of the perovskite film modified with phosphonate compounds. These findings demonstrate that, compared to the phosphate complex protective layer formed in the perovskite film (sample BMDP group) treated with phosphonate compounds alone in Example 2, the perovskite film (sample BMDP-TSA group) provided in Example 1, treated with phosphonate compounds and subjected to a stepwise crystallization annealing process during its crystallization, can regularly fill the grain boundaries of the perovskite grains with the generated phosphate complex protective layer, while some protective layer precipitates on the surface. In contrast, the protective layer precipitates on the surface of the perovskite film when treated with phosphonate compounds alone, and does not regularly fill the grain boundaries of the perovskite grains. Therefore, the perovskite film treated with phosphonate compounds provided in this patent application can passivate the internal defects of the perovskite film, which is beneficial to further improving the stability of the perovskite film.
[0055] To further compare the stability of perovskite films modified with phosphonate compounds, this experimental example further tested the high-temperature stability and high-humidity stability of the perovskite films provided in Examples 1-3.
[0056] The high-temperature stability test conditions involved heating at 85°C in an atmospheric environment for 1600 hours, and the test results were as follows: Figure 7 As shown, Figure 7The results show that after heating, the perovskite film modified with phosphonate compounds provided in Example 1 (sample BMDP-TSA group) maintains the intensity of the main peak (100) at 14.1° well and has less lead iodide (PbI2) precipitation at 12.7°. However, the perovskite film provided in Example 2 (sample BMDP group) has lower peak intensity retention at both 14.1° and 12.7° than the perovskite film modified with phosphonate compounds provided in Example 1 (sample BMDP-TSA group). This indicates that the perovskite film modified with phosphonate compounds provided in Example 1 is heat-resistant and has good stability at high temperatures.
[0057] The high humidity stability test conditions were 4000 hours of storage in an atmospheric environment with 40% humidity. The test results are as follows: Figure 8 As shown, Figure 8 The results show that the perovskite film modified with phosphonate compounds provided in Example 1 can still maintain its ultraviolet-visible light absorption capacity after long-term storage in a high-humidity environment, retaining 83.9% of its initial absorption capacity. In contrast, the perovskite film (sample BMDP group) provided in Example 2 has a lower ultraviolet-visible light absorption capacity than the perovskite film modified with phosphonate compounds (sample BMDP-TSA group) provided in Example 1. High-temperature and high-humidity stability tests on the perovskite film modified with phosphonate compounds confirm that the perovskite film modified with phosphonate compounds provided in Example 1 can maintain its original structure under high-temperature and high-humidity conditions, is not easily decomposed, and has the potential to improve the photoelectric conversion efficiency of solar cells. To further illustrate the film's ability to improve the photoelectric conversion efficiency of solar cells, this application assembles the perovskite film modified with phosphonate compounds provided in Example 1 into a perovskite solar cell and conducts photoelectric efficiency and external quantum efficiency tests.
[0058] Among them, the photoelectric efficiency test was at 100mW / cm 2 The test was conducted under standard light intensity, and the results are as follows: Figure 9As shown, the perovskite solar cell based on the phosphonate-modified perovskite film (sample BMDP-TSA group) provided in Example 1 has a photoelectric conversion efficiency of 24.20%, which is higher than the 22.18% photoelectric conversion efficiency of the perovskite solar cell assembled based on the Control group perovskite film provided in Example 3, and also higher than the 23.8% photoelectric conversion efficiency of the perovskite solar cell assembled based on the BMDP group perovskite film provided in Example 2. Meanwhile, the open-circuit voltage of the perovskite solar cell assembled based on the phosphonate-modified perovskite film provided in Example 1 is 1.17V, and the fill factor is 81.63%, which are also significantly higher than the perovskite solar cells assembled based on the Control group perovskite film provided in Example 3 and the BMDP group perovskite film provided in Example 2. Furthermore, the external quantum efficiency test shows that the integrated current of the perovskite solar cell including the phosphonate-modified perovskite film provided in Example 1 is 25.32 mA / cm². 2 The results are higher than those of the perovskite solar cells assembled based on the Control group perovskite thin films provided in Example 3 and the perovskite solar cells assembled based on the BMDP group perovskite thin films provided in Example 2, which is consistent with the results of the photoelectric efficiency test.
[0059] Through the above performance tests, it can be determined that the preparation method provided in Example 1, by adding the modified additive N-butylsulfonate pyridine phosphate dihydrogen salt and cooperating with the two-stage annealing process, can significantly improve the stability of the perovskite film structure under high temperature and high humidity conditions. Furthermore, after assembling the perovskite film modified with phosphate sulfonate compounds provided in Example 1 into a solar cell, the photoelectric conversion efficiency of the solar cell can be significantly improved. This indicates that this application optimizes the performance of existing perovskite solar cells based on perovskite films.
[0060] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit them. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of this application.
[0061] The above description is only a preferred embodiment of the present invention. It should be noted that for those skilled in the art, several equivalent substitutions, improvements and modifications can be made without departing from the principle of the present invention, and the technical solutions obtained by these equivalent substitutions, improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. A method for preparing perovskite thin films modified with phosphonate compounds, characterized in that, Including the following steps: Step S1: Dissolve lead halide, formamidinium halide and phosphonate compounds in an organic solvent to obtain a phosphonate-modified perovskite precursor solution. Step S2: Spin-coating the perovskite precursor solution modified with phosphonate compounds to prepare a wet film of perovskite precursor modified with phosphonate compounds. Step S3: Anneal the perovskite precursor wet film modified with phosphonate compounds at 50~70℃ for 1~5 minutes to obtain a one-step annealed perovskite precursor wet film modified with phosphonate compounds. Step S4: Anneal the wet film of the perovskite precursor modified by phosphate sulfonate compound in one step at 110~125℃ for 10~40 minutes to obtain the perovskite film modified by phosphate sulfonate compound. The phosphate sulfonate compound is selected from N-butylsulfonic acid pyridine dihydrogen phosphate.
2. The method for preparing a perovskite thin film modified with a phosphonate compound according to claim 1, characterized in that, Step S3 specifically includes: annealing the perovskite precursor wet film modified with phosphonate compounds at 65°C for 1 minute to obtain a one-step annealed perovskite precursor wet film modified with phosphonate compounds. Step S4 specifically includes: annealing the wet film of the perovskite precursor modified by phosphate sulfonate compound at 120°C for 30 minutes to obtain the perovskite film modified by phosphate sulfonate compound.
3. The method for preparing a perovskite thin film modified with a phosphonate compound according to claim 1, characterized in that, In step S1, the lead halide is selected from any one or at least two of lead chloride, lead iodide, and lead bromide; The formamidine halide is selected from any one or at least two of formamidine chloride, formamidine bromide, or formamidine iodide.
4. The method for preparing a perovskite thin film modified with a phosphonate compound according to claim 1, characterized in that, Based on mass parts, in step S1, the perovskite precursor solution modified with phosphosulfonate compounds includes 659.2 parts by mass of lead iodide, 245.9 parts by mass of formamidinium iodide, and 0.43 parts by mass of N-butylsulfonic acid pyridine dihydrogen phosphate.
5. The method for preparing a perovskite thin film modified with a phosphonate compound according to claim 1, characterized in that, In step S2, the perovskite precursor solution modified with phosphonate compounds is spin-coated, specifically by adding the perovskite precursor solution modified with phosphonate compounds and the antisolvent to the substrate and spin-coating it using a spin coater.
6. The method for preparing a perovskite thin film modified with a phosphonate compound according to claim 1, characterized in that, In step S1, the organic solvent is selected from any one or at least two of N,N-dimethylformamide, dimethyl sulfoxide, and isopropanol.
7. The method for preparing a perovskite thin film modified with a phosphonate compound according to claim 5, characterized in that, In step S2, the antisolvent includes any one or at least two of chlorobenzene, anisole, ethyl acetate, and diethyl ether.
8. A perovskite thin film modified with a phosphonate sulfonate compound, characterized in that, It is prepared by the preparation method described in any one of claims 1-7.
9. A photovoltaic cell, characterized in that, It includes a conductive glass substrate, an electron transport layer, a perovskite absorber layer, a hole transport layer, and a metal top electrode, which are stacked sequentially. The perovskite absorber layer comprises the perovskite film modified with phosphonate compounds as described in claim 8.
Citation Information
Patent Citations
Application of compound in solar cell, solar cell and preparation method thereof
CN114373868A
Perovskite composite material, perovskite solar cell and preparation method thereof
CN114497381A
